Justify each step of solving the equation by indicating the property that was used to get to the next step.

– 32 = 2(-2y – 1) + 14y

1. – 32 = – 4y – 2 + 14y

2. 32= 10y – 2

3. 30 = 10y

4. – 3 = y

Justify each step of solving the equation by indicating the property that was used to get to the next step.

– 32 = 2(-2y – 1) + 14y

1. – 32 = – 4y – 2 + 14y

2. 32= 10y – 2

3. 30 = 10y

4. – 3 = y

Answer:Step-by-step explanation:justification for the solution stepsfor …-32 = 2(-2y -1) +14y## Solution

1.-32 = -4y -2 + 14y . . . .distributive property2.-32 = 10y – 2 . . . .collecting terms(like terms can be combined)3.-30 = 10y . . . .addition propertyof equality (2 is added to both sides)4.-3 = y . . . .division propertyof equality (both sides are divided by 10)